2018
DOI: 10.5114/aic.2018.78329
|View full text |Cite
|
Sign up to set email alerts
|

Association of mean platelet volume and red blood cell distribution width with coronary collateral development in stable coronary artery disease

Abstract: IntroductionThe prognostic value of hematological indices in cardiovascular diseases and the association between these parameters and cardiovascular conditions have been established in the literature.AimIn this study, we aimed to investigate the relation of mean platelet volume (MPV), MPV to platelet ratio (MPR) and red cell distribution width (RDW) with degree of coronary collateral development (CCD) in stable coronary artery disease (CAD) subjects with established critical coronary artery stenosis.Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Another examined hematological maker is mean RDW. In one study, it was shown that high RDW and MPV values in patients with SCAD showed a negative correlation with collateral development (22). In our study, we found that RDW and MPV values were significantly higher in the group 1 than in the group 2.…”
Section: Discussionsupporting
confidence: 54%
“…Another examined hematological maker is mean RDW. In one study, it was shown that high RDW and MPV values in patients with SCAD showed a negative correlation with collateral development (22). In our study, we found that RDW and MPV values were significantly higher in the group 1 than in the group 2.…”
Section: Discussionsupporting
confidence: 54%
“…However, elevated RDW may be related myocardial ischemia, as heart failure caused by atherosclerosis of the coronary vessel walls is stimulated by inflammation 9,23,24 . Some studies have shown that RDW is an effective prognostic factor for outcomes in critically ill patients and septic patients [28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…High red cell distribution width (RDW) values are used as a predictor of poor prognosis in many diseases, including cardiovascular diseases, perioperative stroke, malignancies and respiratory diseases 4 8 . Elevated RDW values are associated with adequate collateral development in patients with stable coronary artery disease and perioperative stroke in patients undergoing cardiac valve surgery 9 , 10 . Additionally, high RDW is associated with inflammatory conditions in various diseases, such as Hashimoto’s thyroiditis, rheumatoid arthritis, inflammatory bowel disease and gastrointestinal disorders 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study it has been reported that, MPV of subjects with vitamin D deficiency, another condition that associated with low grade inflammation, have greater MPV values compared to subjects with normal serum vitamin D levels (14). Increased MPV has been also shown in stable coronary artery disease patients who have inadequate coronary collateral development (15). Moreover, MPV has been studied in IBS in literature and authors reported elevated MPV in patients with IBS compared to healthy subjects (16).…”
Section: Introductionmentioning
confidence: 97%